Physicochemical changes in ‘Holland’ papaya fruit treated with quarantine hot water incorporated with salicylic acid dip during cold storage - Supapvanich, S.; Boonyaritthongchai, P.; Wongs-Aree, C. (My University, 2019)
The aim of this study was to determine the effects of quarantine hot water dip at 42°C for 40 min followed with 49°C for 20 min (H) incorporated with 2.0 mM salicylic acid (SA) on physicochemical changes in ‘Holland’ papaya fruit during storage. Firmness, total soluble solids content, electrolyte leakage (EL), malondialdehyde (MDA) content, pectin substances, antioxidant capacity, ascorbic acid and total phenols content of the fruit held at 8±1°C for 21 days followed by 1 day at room temperature (31±2°C) were monitored. The firmness of the fruit dipped in hot water incorporated with 2.0 mM SA (2.0 mM SA+H) dip was higher than that of the fruit dipped in H, 2.0 mM SA and control. All treatments had no effect on TSS content. 2.0 mM SA+H dip retarded the increase in EL, MDA and EDTA-soluble pectin content and decrease in Na2CO3-soluble pectin content better than other treatments. Moreover, bioactive compounds content such as antioxidant capacity, ascorbic acid and total phenols content were maintained by 2 mM SA+H dip. These suggest that the use of 2.0 mM SA+H is an effective alternative maintaining postharvest quality of papaya fruit during cold storage.
Keywords: Bioactive compounds; Firmness; Hot water dip; Papaya fruit; Salicylic acid